Inferring Interbank Loans and Interest Rates from Interbank Payments - an Evaluation - Q. Farooq Akram; Casper Christophersen (Norges Bank, 2013)
We investigate whether overnight interbank loans and interest rates can be reliably inferred at the market and bank level from central banks' interbank payments data. We identify overnight loans and interest rates among interbank payments for 11 banks in Norway and compare them with the actual overnight loans and interest rates reported daily by these banks to the Norwegian central bank since October 2011. We find that interbank payments can provide reliable information about overnight lending and overnight interest rates at the market level, and even at the bank level, for relatively small overnight lenders and large overnight lenders that mostly lend on their own behalf.
hdl:11250/2496677
Keywords: G21; E42; E43; 330; furfine; overnight interbank rates; interbank payments